Two-photon ESIPT-based fluorescent probe using 4-hydroxyisoindoline-1, 3-dione for the detection of peroxynitrite. Issue 84 (7th October 2021) - Wu, Luling; Tian, Xue; Lee, Dong Joon; Yoon, Juyoung; Lim, Chang Su; Kim, Hwan Myung; James, Tony D.
Abstract : Excited-state intramolecular proton transfer (ESIPT)-based fluorophores with two-photon excitation fluorescence (TPEF) are rare. Abstract : Excited-state intramolecular proton transfer (ESIPT)-based fluorophores with two-photon excitation fluorescence (TPEF) are rare. Our aim with this research was to develop ESIPT-based fluorophores exhibiting TPEF. Herein, we used 4-hydroxyisoindoline-1, 3-dione as a scaffold to develop a two-photon fluorescent probe BHID-Bpin, for the detection of peroxynitrite (ONOO − ). BHID-Bpin exhibits excellent selectivity, sensitivity, and fast response towards ONOO − in PBS buffer solution (10 mM, pH = 7.40). Additionally, BHID-Bpin displays high photo-stability under two-photon irradiation at 750 nm. Furthermore, the probe can image endogenous ONOO − in HeLa cells and exogenous ONOO − in rat hippocampal slices at a depth of 110 μm.